Enhancing Spiritual Inclusion: A Systematic Literature Review on the Intersection of Disabilities and Worship Practices Among People with Disabilities - Mohd Zahir Abdul Rahman; Shah Rizul Izyan Zulkiply; Noornajihan Ja‘afar; Siti Fatimah Mohd Tawil; Nurul Asiah Fasehah Muhamad (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA